Spontaneously hypertensive rats exhibit increased liver flavin monooxygenase expression and elevated plasma TMAO levels compared to normotensive and Ang II-dependent hypertensive rats - Gawryś-Kopczyńska, Marta; Szudzik, Mateusz; Samborowska, Emilia; Konop, Marek; Chabowski, Dawid; Onyszkiewicz, Maksymilian; Ufnal, Marcin (Frontiers in Physiology, 2024)
Background: Flavin monooxygenases (FMOs) are enzymes responsible for the oxidation of a broad spectrum of exogenous and endogenous amines. There is increasing evidence that trimethylamine (TMA), a compound produced by gut bacteria and also recognized as an industrial pollutant, contributes to cardiovascular diseases. FMOs convert TMA into trimethylamine oxide (TMAO), which is an emerging marker of cardiovascular risk. This study hypothesized that blood pressure phenotypes in rats might be associated with variations in the expression of FMOs. Methods: The expression of FMO1, FMO3, and FMO5 was evaluated in the kidneys, liver, lungs, small intestine, and large intestine of normotensive male Wistar-Kyoto rats (WKY) and two distinct hypertensive rat models: spontaneously hypertensive rats (SHRs) and WKY rats with angiotensin II-induced hypertension (WKY-ANG). Plasma concentrations of TMA and TMAO were measured at baseline and after intravenous administration of TMA using liquid chromatography-mass spectrometry (LC-MS). Results: We found that the expression of FMOs in WKY, SHR, and WKY-ANG rats was in the descending order of FMO3 > FMO1 >> FMO5. The highest expression of FMOs was observed in the liver. Notably, SHRs exhibited a significantly elevated expression of FMO3 in the liver compared to WKY and WKY-ANG rats. Additionally, the plasma TMAO/TMA ratio was significantly higher in SHRs than in WKY rats. Conclusion: SHRs demonstrate enhanced expression of FMO3 and a higher plasma TMAO/TMA ratio. The variability in the expression of FMOs and the metabolism of amines might contribute to the hypertensive phenotype observed in SHRs